Evaluating Antibiotics Administration’s Pattern and Its Financial Burden in a Teaching Hospital in Iran: Antibiotics Administration’s P attern in Hospital - Esmaeil Soufian, Pouria; Bagheri, Mahdi; Cheraghali, Abdol Majid (Iranian Journal of Pharmaceutical Sciences, 2021)
Indiscriminate use of antibiotics frequently leads to healthcare complications, including an increase in the number of resistant microorganisms and patient hospitalization period, which subsequently results in a financial disadvantage for the patients and the country’s healthcare system. Therefore, researches on causes of such malpractices could shed light on ways to prevent further impacts on health care system. The purpose of this study is to investigate antibiotics administration’s pattern and its financial burden in a teaching hospital in Iran in 2018. This descriptive cross-sectional study is based on data obtained from the hospital medicine statistics unit. The share of antibiotics in the total cost of medicine expenditure has been calculated and the cost burden of top 10 antibiotics and their administration in different hospital departments were also assessed. According to the data obtained, about 12.2% of the total cost of medication expenditure in the hospital in 2018 was attributed to the administered antibiotics. The financial burden due to the use of all medicines and antibiotics in 2018 per patient admitted in the hospital were 4,327,912 Rials (1,030 USD) and 529,400 Rials (126 USD), respectively. The total use of these antibiotics was 56.77 DDD/100Bed-Days. Financial burden of the injectable forms of antibiotics is higher than other pharmaceutical forms and the intensive care unit showed the most use of these antibiotics. The 10 most high-cost administered antibiotics included Meropenem, Ciprofloxacin, Clindamycin, Vancomycin, Teicoplanin, Levofloxacin, Metronidazole, Azithromycin and Ceftriaxone, respectively. Compared to the other published data regarding administration of antibiotics in other hospitals, this study showed that there is a need for more surveillance on rational administration of the antibiotics in this hospital.